Soucasná problematika zardĕnek v Armádĕ Ceské republiky - Jirous, J; Machula, F (Epidemiologie, mikrobiologie, imunologie, 1998)
The authors evaluate the proportion of subjects susceptible to rubella infection based on serological investigations and the possible development of epidemics in units of the Czech Army. New aspects of the problem of rubella are outlined: a higher incidence of the disease in adolescents and young adults, possible re-infection, loss of typical cyclic character of epidemics in the Czech Army, incidence of new complications among conscripts and suggested provisions for prevention and in the event of occurrence of the disease in army units.
Keywords: Rubella virus; mladiství; virus zarděnek; séroepidemiologické studie; dospělí; Seroepidemiologic Studies; Adult; lidé; protilátky virové; Military Personnel; Czech Republic; Adolescent; Rubella; Antibodies, Viral; ozbrojené síly; Humans; zarděnky; Česká republika